Aggregation‐Induced Emission Luminogens Married to 2D Black Phosphorus Nanosheets for Highly Efficient Multimodal Theranostics. Issue 37 (6th August 2020) - Huang, Jiachang; He, Benzhao; Zhang, Zhijun; Li, Youmei; Kang, Miaomiao; Wang, Yuanwei; Li, Kai; Wang, Dong; Tang, Ben Zhong
Abstract: Inspired by the respective advantages of aggregation‐induced emission (AIE)‐active photosensitizers and black phosphorus nanomaterials in cancer treatment, the facile construction of novel AIE photosensitizers married to 2D black phosphorus nanosheets and their application for multimodal theranostics are demonstrated. The developed nanomaterial simultaneously possesses distinctive properties and multiple functions including excellent stability, good biocompatibility, intensive fluorescence emission in the NIR region, high‐performance reactive oxygen species generation, good photothermal conversion efficiency, outstanding cellular uptake, and effective accumulation at the tumor site. Both in vitro and in vivo evaluation show that the presented nanotheranostic system is an excellent candidate for NIR fluorescence–photothermal dual imaging‐guided synergistic photodynamic–photothermal therapies. This study thus not only extends the applications scope of AIE and black phosphorus materials, but also offers useful insights into designing a new generation of cancer theranostic protocol for potential clinical applications. Abstract : A novel multifunctional theranostic nanoplatform based on both aggregation‐induced emission luminogens and 2D black phosphorus nanomaterials is successfully developed. The presented hybrid nanotheranostic system possesses distinctive properties, endowing it with excellent performance for in vitro and in vivo cancer theranostics involving NIR fluorescence–photothermal dual‐imaging‐guided synergistic photodynamic–photothermal therapies.